The effect of bioactive polyphenols from anacardium occidentale linn. Leaves on α-amylase and dipeptidyl peptidase iv activities - Abdullah Thaidi, Nur Imanina; Mat Jusoh, Hanapi; Ghazali, Ahmad Badruddin; Darnis, Deny Susanti; Haron, Normah (Gadjah Mada University, 2020)
Anacardium occidentale Linn. (A. occidentale L.) leaves possess an excellent source of bioactive compounds, which are associated with numerous health benefits including antidiabetic potency for the management of type 2 diabetes mellitus (T2DM). The management strategies for T2DM include to maintain the postprandial blood glucose level through the in